Duszpasterski i kanoniczny wymiar wizytacji parafii - Dyduch, Jan (Prawo Kanoniczne, 2001)
The canonical visitations of parishes are the essential instrument of the bishop’s pastoral ministry. The legislator requires to conduct them systematically in such a way that the entire diocese could be visited during the period of five years. Subjects to the visitations are persons, Catholic institutions, also sacred places and objects remaining on the territory of the given parish. The parish visitation should become the joint pastoral action of the bishop, the priests, the religious and the laity; action permeated with loving concern for souls. The bishop inspects all departments of apostolate and pastoral ministry in the parish, its administration and financial status. During his visitation, the bishop performs his mission of teaching, sanctifying and governing.